2007
DOI: 10.1177/0115426507022006664
|View full text |Cite
|
Sign up to set email alerts
|

The Role of an Intravenous Fat Emulsion Composed of Fish Oil in a Parenteral Nutrition‐Dependent Patient With Hypertriglyceridemia

Abstract: Hypertriglyceridemia is a common complication in patients receiving parenteral nutrition (PN). Management typically involves withholding the IV fat emulsion (IVFE) until serum triglyceride levels normalize. In some instances, this practice may predispose patients to the development of essential fatty acid deficiency (EFAD) unless alternative therapies such as oral or topical oils are used. This is especially true in patients unable to tolerate enteral intake. We describe the management of hypertriglyceridemia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 58 publications
1
20
0
1
Order By: Relevance
“…We have also shown that fish oil-based lipid emulsion can be effective as a sole fat source in cases of hypertriglyceridemia or when standard soybean-based emulsions are contraindicated (9, 10). It should be noted that although both emulsions are primarily constituted of a single fatty acid type (omega-6 or omega-3), they are not a pure fatty acid subtype formulation and both possess some amount of the other (primarily omega-6 + some omega-3, primarily omega-3 + some omega-6).…”
mentioning
confidence: 88%
“…We have also shown that fish oil-based lipid emulsion can be effective as a sole fat source in cases of hypertriglyceridemia or when standard soybean-based emulsions are contraindicated (9, 10). It should be noted that although both emulsions are primarily constituted of a single fatty acid type (omega-6 or omega-3), they are not a pure fatty acid subtype formulation and both possess some amount of the other (primarily omega-6 + some omega-3, primarily omega-3 + some omega-6).…”
mentioning
confidence: 88%
“…The aforementioned studies using fish oil as the sole source of fat in a subset of pediatric patients dependent on PN showed that their EFAD reversed, liver function improved, and growth was maintained (47). However, there is still skepticism regarding the ability of a fish oil-based diet, when used as monotherapy, to prevent EFAD and maintain adequate growth rate (48-50).…”
Section: Fish Oil Prevents Essential Fatty Acid Deficiencymentioning
confidence: 99%
“…In contrast with OM3 EE forms that require this digestive step, the free fatty acid forms of omega-3 are not dependent on pancreatic enzyme activity512 and are readily absorbed, so have improved bioavailability that is less dependent on meal fat content 13. A novel free fatty acid formulation of omega-3 (OM3 FFA, Epanova™, Omthera Pharmaceuticals Inc, Princeton, NJ, USA) was developed to maximize the bioavailability of the omega-3 fatty acids, eicosapentaenoic acid (EPA) and docosahexaenoic (DHA), in patients with hypertriglyceridemia who are advised to restrict fat intake 3.…”
Section: Introductionmentioning
confidence: 99%